EFFECTS OF USING COMMUNICATIVE ACTIVITIES TO ENHANCE THE SPEAKING SKILLS OF ELEMENTARY STUDENTS - Aksoy, Yeşim (Revista Inclusiones, 2019)
This study examines and reports on the effects of using communicative activities to enhance the speaking skills of elementary students studying in the Preparatory School of Near East University. It analyzes the responses of students (n=100) who are currently studying in the Preparatory School and the instructors (n=33) who are currently employed as English language teachers in Preparatory school. The study addresses five issues: How is CLT (Communicative Language Teaching) implemented in the Preparatory School of NEU (Near East University) and what are the effects of the newly implemented communicative activities on the elementary students‟ performance in speaking? What is the role and place of speaking in learning English as a foreign language in the Preparatory School of NEU and what are the students‟ and teachers‟ opinions about the speaking skill in terms of students‟ needs? What are the factors that prevent the elementary students in Preparatory School from speaking? How can elementary students in Preparatory School be assisted to participate more in communicative activities that focus on speaking? And finally, How do students perceive the communicative activities used in the class to enhance their speaking skills? Detailed student and teacher questionnaires, feedback forms and observation forms were used to investigate the effect of using communicative activities to enhance the speaking skills of elementary students studying in the Preparatory School of Near East University. The findings indicate that it is necessary to use extra communicative activities and materials besides the ones in the students‟ books to help and encourage students to use the language accurately and fluently outside the classroom and continue their careers in the real community. Moreover, carrying out communicative activities in the classroom gives an opportunity to the students to act in real life situations and use English accurately and fluently. These activities also encourage them to join in the activities and explain their ideas to their classmates to develop their communication skills. The findings of this article suggest that before designing an English teaching syllabus based on the students‟ level, it is important to find out the students‟ interest and design activities to develop students‟ communication skills in learning English.